Character Education for Elementary School Students: Creative, Ecological Conscious, and Communicative - Wandari, Icha Olvi; Rohana (Indonesian Values and Character Education Journal, 2023)
This research aimed at examining character education for elementary school students in the NA.IX-X district is located of North Labuhanbatu Regency in terms of their creative character education, care for the environment, and friendly/communicative character. This research employed qualitative methodby descriptive approach.The sampling technique uses the slovin formula 150 respondents and key informants for grade 5 teachers. The instruments used for research were questionnaires and interviews. Data analysis include data reduction, data analysis, and conclusion drafting. Regarding the application of creative characters in the adequate category with a percentage of 44,53%, it has been demonstrated that students' creative characters are able to ask questions when there are learning difficulties through the use of declarative sentences. If there is content that they do not understand, they will always question the teacher until they do, as it is an added value that teachers provide to students who frequently ask questions. In addition, students' behavior in forming care for the environment behavior in this category is sufficient with a percentage of 75.99% indicating that trash is disposed of properly.Friendly/communicative character with a percentage of 44.53% indicates that elementary school students in Na district IX-X speak politely. According to teacher interviews, teachers constantly monitor students, particularly in terms of communication.